Microscale Technologies for Cell Engineering - Singh, Ankur; Gaharwar, Akhilesh K. (Springer International Publishing : Imprint: Springer, 2016)
This book offers readers cutting-edge research at the interface of polymer science and engineering, biomedical engineering, materials science, and biology. State-of-the-art developments in microscale technologies for cell engineering applications are covered, including technologies relevant to both pluripotent and adult stem cells, the immune system, and somatic cells of the animal and human origin. This book bridges the gap in the understanding of engineering biology at multiple length scale, including microenvironmental control, bioprocessing, and tissue engineering in the areas of cardiac, cartilage, skeletal, and vascular tissues, among others. This book also discusses unique, emerging areas of micropatterning and three-dimensional printing models of cellular engineering, and contributes to the better understanding of the role of biophysical factors in determining the cell fate. Microscale Technologies for Cell Engineering is valuable for bioengineers, biomaterial scientists, tissue engineers, clinicians, immunoengineers, immunologists and stem cell biologists, as it offers a review of the current cutting-edge cell engineering research at multiple length scale and will be valuable in developing new strategies for efficient scale-up and clinical translation.